Fauna living in colonies of Mussismilia hispida (Verrill) (Cnidaria: Scleractinia) in four South-eastern Brazil islands - Nogueira,João Miguel de Matos (2003)
Colonies of Mussismilia hispida were collected in four south-eastern Brazil islands and fixed in formalin. Volume, living and basal areas of each coral head were measured. Animals found over, under and inside the corals were sorted, resulting in 9657 specimens belonging to more than 130 taxa. The underside of the colonies was occupied by bivalves and colonial forms of sponges, bryozoans and ascidians. On the living surface, barnacles and cryptochiridean crabs were detected. The endolithic animals included polychaetes, bivalves and sipunculid worms. Most of the animals collected were vagile microcrustaceans. In general, the corals in this ecosystem: (1) act as a nursery place for the community; (2) provide protection for many species also found in other habitats; (3) support a community mainly omnivorous and detritivorous; (4) are initially colonised randomly.